Complimentary Diagnostic Tools for Endometrosis in Biopsies of Mares with Clinical Subfertility - Rojas, Daniela; Cabezas, Joel; Ramírez, Ghyslaine; Saraiva, Fernando; Lleretny, Rodriguez-Alvarez; Ovidio Castro, Fidel (Acta Scientiae Veterinariae, 2020)
Background: Endometrosis is a multifactorial disease and one of the main causes of infertility in mares, its etiology and pathogenesis are not completely understood. It is defined as peri glandular and/or stromal endometrial fibrosis with glandular alterations. Due to the few clinical symptoms, besides anamnesis and fertility data, endometrosis requires histological confirmation. The histo-morphology and immune histochemical characteristics of the endometrium vary among individuals according to the disease progression. The aim of this research was to combine histology with new immune and histochemical tools for a more precise detection of fibrotic changes of mares with endometrosis. Materials, Methods & Results: The endometrium of forty thoroughbred mares aged 5-18 years, that did not become pregnant during the last two breeding seasons in a Chilean commercial equine breeding center were biopsied. Samples were subjected to conventional histopathology with hematoxylin-eosin as well as to specific histological staining using specific techniques such as Alcian blue and Masson Fontana, aimed to ascertain what types of mucopolysaccharides were present in those samples. In order to have a deeper picture of the progression of the pathology, immune histochemical methods for the detection of vimentin, cytokeratin, progesterone receptor and lymphocyte marker CD3 were used. Finally in order to detect fibrillar collagen we used second harmonic generation (SHG) technique with detects fibrillar collagen without staining, due to intrinsic hyperpolarization ability of this type of collagen, which can be detected by atomic force microscopy. As a result of our research samples were categorized according to the scale of Keeney and Doig into categories I, IIa, IIb and III (45, 42, 7.5 and 5% respectively). These samples also were characterized by the methods listed earlier and a result we found specific staining in 15 samples coming from higher endometrial damage using Masson-Fontana, while acid staining indicative of acid mucopolysaccharides were detected in 97% of the samples. At immunostaining, we found cytokeratin and vimentin differentially expressed as a function of the degree of the lesions. Cytokeratin was detected in glands from healthy mares, but it was almost absent as the injury was increased. Vimentin in turn, was detected in 26 samples with different degree of intensity. In nine animals, vimentin expression was anomalous, and the marker was detected in fibrotic foci concentrically surrounding glands in biopsies of grade I and IIA only. Although progesterone receptor was detected, there was no correlation with endometrosis. Finally, the lymphocyte T specific CD3 marker was positive in 100% of cases analyzed in which moderate lymphocytic infiltration was found by hematoxylin-eosin; however no staining could be detected in mares with more advanced endometrosis. By combining immunofluorescence with the detection of second harmonic it was possible to detect in the same sample two proteins and collagen deposition at the same time, this had not been reported earlier for endometrosis and mares. Discussion: Our results suggest that the combination of the different methods mentioned is useful for validation and further characterization of the routine hematoxylin-eosin, and can be used as a complementary tool for the diagnosis. Of value, it was possible to combine immunofluorescence with SHG in a single sample in situ.